Growth Status and Glycemic Control of Diabetic Children in a Tertiary Care Hospital in Dhaka City - Naz, Farzana; Tayyeb, Samin; Zabeen, Bedowra; Choudhury, Adnan Yusuf (Mugda Medical College Journal, 2024)
Childhood growth is a critical indicator of the health status of a child which also determines the overall developmental potential in adult life. Along with an increased risk of developing various co-morbidities, diabetic children remain susceptible to growth delay in terms of height and weight. Thus it is necessary to evaluate their growth status about their glycemic control. This cross-sectional study observed 148 sequentially selected diabetic children aged 9 to 15 years, with 5 years of diabetes duration attending a tertiary level hospital. Data regarding their anthropometric measurements including height and weight, HbA1c status, and diabetic history has been collected. HbA1c level is a significant determinant of height, weight, and BMI of the study subjects (p<0.05). The age at diagnosis of diabetes was found to have a significant impact on the height of the girls and weight of both boys and girls and also on their HbA1c level, where, in all groups, the age at diagnosis at 5 to 9 years found to have the highest proportion of children whose growth was less than the reference range. The duration of diabetes in this study was not related to the anthropometric measurement of the children (p>0.05) although it was significantly associated with their HbA1c level (p<0.05). This study's results observed growth alteration among children with diabetes in association with their HbA1c level and age at diagnosis, which suggests that diabetic children should undertake routine monitoring of growth and glycemic control to provide timely and adequate interventions to prevent growth delay among them. Mugda Med Coll J. 2023; 6(2): 88-92